Impementing quality systems in a foundry - Bosch, Cyril Henry (My University, 2016)
he purpose of this project was to introduce an affective Quality Control Systems into a newly established foundry. The parent company expressed concern about the poor quality of locally produced castings and decided to invest in it's own foundry. As the company exclusively produces components for the motor manufacturing industry it was of paramount importance that the foundry is equipped and run in accordance to the high manufacturing standards set by the major motor manufactures. As the Auto Industrial Group is committed to a total Quality Control programme in line with the high-tech motor manufactures it is obvious that the foundry follow suite. The strategy adopted was to base a Quality management system along the lines of SABS 0157 and to expand it to ensure that all the quality requirements of the customers are accommodated
A project report submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Engineering. Johannesburg, 1991
Keywords: Quality control